Determinants of breast cancer among women attending oncology units in selected health facilities of Hawassa City, Sidama Region, Southern Ethiopia, 2023: case-control study - Kebede, Selamawit; Alemu, Tsegaye; Mekonnen, Ashenafi (Frontiers in Oncology, 2024)
Background: The incidence of breast cancer is rampantly increasing in developing countries, particularly Ethiopia. Unfortunately, the morbidity and mortality rates are sharply increasing, and because of this, families are suffering from socioeconomic crises. Despite this, there is limited evidence on the determinants of breast cancer in Ethiopia as well as in the study area. Objective: To identify the determinants of BC among women attending oncology units in Hawassa city, Hospitals Hawassa, Ethiopia, in 2023. Method: A hospital-based, case‒control study with 300 patients (75 patients and 225 controls) was carried out in Hawassa from June to July 2023. A simple random sampling technique was used to select cases and controls. The data were collected via pretested and structured digitally installed questionnaires with Kobo collection/smartphones. The data were exported from the server to SPSS version 27 for analysis. Descriptive analysis of univariate, bivariate, and multivariable logistic regression data was conducted to determine the associations between breast cancer incidence and independent factors. Results: A total of 300 women participated in this study, for a response rate of 100%. The mean (+SD) ages of the respondents were 37.2 (+14.8) and 36.6 (+15.1) years for the cases and controls, respectively. According to the multivariate logistic regression model, postmenopausal status (AOR: 2.49; 95% CI [1.18, 5.23]), family history of cancer (AOR: 2.33; 95% CI [1.12, 4.82]), oral contraceptives (AOR: 2.74; 95% CI [1.34, 5.99]), overweight and/or obesity (AOR: 2.29; 95% CI: 1.14, 4.59), and consumption of solid oil (AOR: 2.36; 95% CI [1.20, 4.67]) were independently associated with BC risk. Conclusion: This study revealed important risk factors for BC. Therefore, women should adopt healthier lifestyles through healthy nutrition and regular exercise to reduce the risk of developing BC. In addition, early detection and regular screening are proactive approaches for detecting BC.